Discrete time to event with random effect model using Malaysian graduate employability data - Rahmattullah Khan Abdul Wahab Khan (Tanjong Malim, 2019)
Discrete time to event with random effect model using Malaysian graduate employability data by Rahmattullah Khan Abdul Wahab Khan